DISTRIBUSI DAN KARAKTER SITUS-SITUS NEOLITIK DI KECAMATAN BANTARKALONG DAN KARANGNUNGGAL, TASIKMALAYA, JAWA BARAT - Retno Handini (BRIN, 1999)
The pattern of workshop sites from the neolithic culture which is located not far from the river–and especially in Bantarkalong and Karangnunggal Subdistricts along with the technological character–reminds us of other similar sites such as the stone bracelet workshop sites in Limbasari and Ponjen (Purbalingga) areas, which are generally also near streams. This can be understood, because at that time, rivers played a very important role for human life, both for transportation and for meeting their daily water needs, so that their shelter was always strived to be close to water sources. Especially during the Neolithic era, they have started to apply farming methods, so that the need for water is very high.